The benefits of outdoor orientation programming in higher education and recommendations for the development of an outdoor orientation program at Kansas State University - Huber, Gerald E. (Kansas State University, 2012)
Outdoor orientation programs (OOPs) have the same goal as traditional first-year student orientation programs (e.g., First-Year Seminar), that is, helping facilitate the transition of first-year students to collegiate life. There are many challenges first-year students face while transitioning into college. Research shows that OOPs can increase retention rates of first-year students; help first-year students to grow personally, socially and spiritually; and increase friendship formation among this population (Davis-Berman & Berman, 1996; Devlin, 1996; Galloway, 2000). Today, there are approximately 164 higher education institutions in the United States that offer OOPs to their first-year students. Currently, Kansas State University has several programs that aid students in their transition to collegiate life. However, they do not currently have an OOP in place. A survey was conducted at Kansas State University to evaluate the level of interest in an OOP and/or an outdoor trips program. Survey results suggest that there are a significant number of current students on campus who would have participated in an OOP if one were offered when they first arrived. Recommendations for the development of an OOP at Kansas State University are made utilizing survey results and interviews with successful OOP program directors at several universities.
Keywords: Outdoor Orientation Program; Pre-Orientation Program; Higher Education (0745)